Diagnóstico de los procesos dinámicos en el río frío, derivados del desarrollo urbano en el municipio de Chía, departamento de Cundinamarca (2019)
Diagnosis of multitemporal housing construction processes, where the changes occurred to the Río Frío water body, in the municipality of Chia Cundinamarca, are evidenced